Modeling of the Layered Hydraulic Fracturing Process for Enhanced Reservoir Performance - Rahmani , Shirullah; Mahboob, Nasratullah; Hanif, Ruhullah (Indonesian Journal of Green Chemistry, 2025)
For over the last ten years, the Tanatar oil and gas field has seen considerable reduction, therefore highlighting the urgent need for efficient stimulation methods to bring reservoir production back up. The fundamental issue under investigation here is the deteriorating performance of already existing wells and the dearth of comprehensive modeling analyses analyzing hydraulic fracturing under the particular geological circumstances of the site. This paper aims to investigate the hydraulic fracturing technique employing an sophisticated numerical modeling technique able of simulating interparticle dynamics, fracture initiation, propagation behavior, and fluid–solid interactions. The research reproduces the microscopic phenomena controlling hydraulic fracturing using a discrete-element-based modeling technique combined with fluid flow simulation. Representative reservoir characteristics were employed to calibrate the computational model, which then simulated stress distribution, crack development, pressure evolution, and resultant changes in permeability. Under several operational scenarios, this approach enables precise prediction of fracture geometry and reservoir reaction. According to the data, wellbore deliverability is improved and hydraulic fracturing greatly increases permeability inside the low-productivity zones of the Tanatar field. The simulations show obvious correlations between injection pressure, fracture propagation patterns, and stimulated reservoir volume. Moreover, the modeling shows that effective and secure extension of the economic life of exhausted reservoirs via hydraulic fracturing is conceivable. To conclude, the study offers the first thorough numerical evaluation of hydraulic fracturing for the Tanatar field and shows its great possibility as a productivity-enhancing strategy. The results give field operations useful direction and support the use of hydraulic fracturing as a practical stimulation technique in comparable low-permeability formations.